PENERAPAN GOOGLE CLASSROOM UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MATERI POKOK PEWARISAN SIFAT MAKHLUK HIDUP - Pratama, Ferry Yudha (Pendidikan Biologi Universitas PGRI Ronggolawe Tuban, 2021)
SMP Muhammadiyah 9 Bojonegoro in the 2020/2021 academic year is implementing an online learning process to face the Covid-19 pandemic. At first, this school implemented an online learning process using WhatsApp group but, the students learning outcomes were not optimal, so the researcher initiative to implement Google Classroom as an online learning process. This research aims to improve student learning outcomes by using Google Classroom on the heredity of living things topically. The type of this research is classroom action research that is carried out in two cycles. Each cycle consists of four stages, are planning, implementing, observing, and reflecting. The research subjects were students of class IX-A SMP Muhammadiyah 9 Bojonegoro, in which a total of 32 students. The research instrument used to collect data was a learning outcome test. The result showed that 71,88% of students could achieve reach KKM in 1st cycle, then 2nd cycle percentage of students who could reach KKM had increased to 93,75%. Based on the result of this study, it can be concluded that the application of Google Classroom can improve the learning outcome of class IX-A SMP Muhammadiyah 9 Bojonegoro 2020/2021 academic year students at heredity of living things topic.